Seismic stratigraphy and development of a modern isolated carbonate platform (Xuande Atoll) in the South China Sea - Liu, Y.; Wu, S.; Li, X.; Chen, W.; Han, X.; Yang, C.; Qin, Y.; Huang, X.; Yang, Z.; Sun, J.; Zhu, L. (Frontiers in Earth Science, 2023)
Xuande Atoll is an isolated carbonate platform that has developed since the early Miocene. To understand the internal structure and development of the atoll, we conducted high-resolution seismic surveys and shallow drilling. Five seismic sequences were observed (from bottom to top): SQ1 (early Miocene), SQ2 (middle Miocene), SQ3 (late Miocene), SQ4 (Pliocene), and SQ5 (Quaternary). The seismic data indicate that platform formation initiated in the early Miocene and flourished during early and middle Miocene. The platform shrank before the isolated platform formed in the middle Miocene. The final shrinking stage occurred in the southern and western parts of the platform at the end of the Miocene, which may reflect rapid tectonic subsidence and increased terrigenous sediment inputs owing to the formation of the semi-marginal sea. The peri-platform contains a falling sea-level sequence that was dominated by mass wasting deposits.